SYNTHESIS AND BIOLOGICAL EVALUATION OF NOVEL THIAZOLE-PYRAZOLE INTEGRATED CHALCONES AS ANTIOXIDANT AND ANTI-INFLAMMATORY AGENTS - DNYANESHWAR SIRSAT; PRADEEP KATE; MADHUSUDAN BACHUTE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present study was to synthesize the thiazole-pyrazole integrated chalcones and their in vitro antioxidant and anti- inflammatory evaluation. Methods: The designed hybrid thiazole-pyrazole integrated chalcones (3a-j) were synthesized by Claisen–Schmidt reaction of substituted 1-(4-methyl-2-phenylthiazol-5-yl) ethanone and substituted pyrazole aldehyde in the presence of 10% NaOH in ethanol solvent under reflux condition. The chemical structures of synthesized compounds were confirmed by IR, 1H nuclear magnetic resonance (NMR), 13C NMR, and high- resolution mass spectra. Results: All the title compounds were screened for their in vitro antioxidant and anti-inflammatory activity. The screening data indicated that tested compounds showed potent antioxidant activity with moderate anti-inflammatory potential. Conclusion: Antioxidant screening data reveal that most of the synthesized compounds possess excellent 1,1-diphenyl-2-picrylhydrazyl and NO radical scavenging activity. Most of the compounds found to possess marked anti-inflammatory potential by effectively inhibiting the heat-induced albumin denaturation.